PUSAT PEMELIHARAAN KESEHATAN, KECANTIKAN, DAN KEBUGARAN KHUSUS WANITA DENGAN KONSEP HEALING ENVIRONMENT DI SURAKARTA - Aini Azizati; Agung Kumoro Wahyuwibowo; Hari Yuliarso (ARSITEKTURA, 2016)
Modern women in urban areas with high mobility, tend to be easily stress and then impact on her body fitness, beauty, and even her health. Stress has become part of modern human life, and one way to cure it is with relaxation. Nowadays not only the beauty treatments but also health care are also sought by women. There is connection between beauty and health, because they’re influence and rely on each other. Beauty basically will decrease and fade, if their body not health, and vice versa. Modern women who has little time, requires an efficient and practical way of treatment to relaxation her body. This issue bring the idea to design a special space to fulfill of women needs, where is consist of health, beauty, and fitness care center. The formulation of the problems in this design is to realize six principles of healing environment. This care center is designed as a place that provides a variety of women needs from health, beauty, fitness, and also as a relaxation space. So it requires a comfortable and quiet atmosphere. Healing environment was selected as the method of design concepts, so can be expected to provide quiet atmosphere, and also can accommodate visitors to help the healing process both physically and psychologically, so that visitors can get fitter. The application of  healing environment concept applied trough nature texture and material so can give perseption to visitors to feel close with nature,  and health colour applied in interior trough furniture or wall colour. The application of  healing environment concept in exterior applied trough healing garden with variety and colours of vegetation in exterior. Keywords:  Care Center, Healing garden, Healing environment, Surakarta.